• 100 of Paulo Freire: an interview with Moacir Gadotti - Soares, Ismar de Oliveira (Comunicação & Educação, 2022)
In October of this year, Moacir Gadotti turned 80 in full activity. Author of several works and owner of an extensive curriculum, the professor holds a teaching degree in Pedagogy and Philosophy, is Master in Philosophy of Education from PUC-SP, a PhD in Educational Sciences from the University of Geneva, Switzerland, and an associate professor at the University of Campinas. Currently, Gadotti is retired from the Faculty of Education of the USP and is an honorary president of the Paulo Freire Institute, where he has worked since 1991. In this interview with Ismar Soares, the author performs a historical recovery of the trajectory of Paulo Freire, with whom he shared a long friendship. Gadotti also reports his impressions on the author and his works, explaining how the Institute revisits Paulo Freire when thinking future education from Freire’s praxis.